The Sustainability Prospective of Irrigation System Management in Bali and Outside of Bali - Gede Ustriyana, I Nyoman; Budiasa, Wayan; Widhianthini, Widhianthini; Punia, I Nengah (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 3 (2021): Vol.15, No.3, 2021, 2021)
Effective and efficient water resources management is unquestionably required to meet the high demand of water to support rapid population growth and socio-economic expansion. The water supply availability is slowly decreased due to plantation land clearing, construction projects, and land-change activities in the watershed area. This study aimed to analyze the sustainability of irrigation management in Bali and outside of Bali (Bolaang Mongondow Regency, North Sulawesi). Primary and secondary data were employed in this study. In-depth interview and focus group discussion sessions conducted to collect the primary data. The literature review technique applied to gather secondary data to support the study result and discussion. We recruited the committee of subak, farmers, and stakeholders or policymakers from the Local Board of Agriculture and Public Works and Public Housing (sub-irrigation division) to participate in this study. Multi-Dimensional Scaling method employed to analyze the study data. Results revealed that the sustainability prospective of the irrigation system management in Mongondow was relatively weak, especially on the physical-ecological, infrastructure-technology, and policy-institutional dimensions. However, we noticed that the economy and social dimension of the watershed area was relatively sustainable. Contrary situations were found on Saba Watershed in Buleleng Regency, Bali Province. We found that the sustainability prospective on the physical-ecological and infrastructure-technology dimension was relatively weak. But the dimension of the economy, socio-cultural, and policy-institutional was adequately sustainable.